2022
DOI: 10.1039/d2py00483f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in asymmetric organocatalysis based on helical polymers

Abstract: Helical polymers have attracted increasing attentions in recent years because of their extensive applications in many fields inculding chiral recognition and seperation, asymmetric catalysis, circularly polarized luminescence, liquid crystallization and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…recent years, many groups including Suginome, Yashima, Gellman, and others have reported helical polymers in the application of asymmetric catalysts. [51,[186][187][188][189][190][191][192][193] Suginome et al reported helical poly(quinoxaline-2,3-diyl)s bearing metal-binding sites could be used as chiral ligands for asymmetric hydrosilylation of styrenes, due to the high purity for a one-handed screw sense and stability. [186] Subsequently, the same group synthesized a similar polymer-based catalyst by "Majority-Rules".…”
Section: Chiral Liquid-crystalline Elastomermentioning
confidence: 99%
“…recent years, many groups including Suginome, Yashima, Gellman, and others have reported helical polymers in the application of asymmetric catalysts. [51,[186][187][188][189][190][191][192][193] Suginome et al reported helical poly(quinoxaline-2,3-diyl)s bearing metal-binding sites could be used as chiral ligands for asymmetric hydrosilylation of styrenes, due to the high purity for a one-handed screw sense and stability. [186] Subsequently, the same group synthesized a similar polymer-based catalyst by "Majority-Rules".…”
Section: Chiral Liquid-crystalline Elastomermentioning
confidence: 99%
“…Bio(macro) molecules, for example, nucleic acids, polysaccharides, and amino acids, adopt chiral structure with sophisticated functions. Such biological systems have inspired scientists to design and construct artificial chiral materials for the applications of separation, [1][2][3][4] catalysis, [5][6][7] and sensing, [8][9][10] etc. [11][12][13][14] To be specific, researchers have approached chiral matter in terms of their photophysical properties, including circular dichroism (CD) and circularly polarized luminescence (CPL) which provide chiral information in ground and excited states, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The helix is an essential secondary structure in biomacromolecules and ubiquitous in nature, playing an important role in living systems. Inspired by nature, scientists, especially chemists, have designed and prepared various helical polymers. Among them, helical poly­(phenyl isocyanide)­s (PPIs) exhibit a stable helical structure and have attracted great attention because of their wide applications in chiral separation, chiral recognition, asymmetric catalysis, etc. PPIs are commonly prepared using Ni­(II), Rh­(III), or Pd­(II) complexes. Among them, Pd­(II) complexes are air-stable and highly active. Because the Pd(0)/ t -Bu 3 P system can initiate the polymerization of relevant fluorine monomers to afford Pd­(II)-terminated PF, this Pd­(II)-containing PF could be expected to serve as a catalyst for the polymerization of phenyl isocyanide monomers, rendering functional PF- b -PPI copolymers, exhibiting distinctive optical properties and self-assembly behavior.…”
Section: Introductionmentioning
confidence: 99%